Evaluation of Maternal Role Adaptation in Mothers with Late-preterm Infants and its Related Factors - Rajabi A; Maleki A; dadashi M; Karamitanha F (Zanjan University of Medical Sciences and Health Services, 2018)
Background: Mothers with preterm infants experience numerous stressful problems which can be associated with negative effects on maternal role adaptation. Objectives: The present study aimed to evaluate maternal role adaptation in mothers with late-preterm infants and its related factors. Methods: This descriptive-analytical study was conducted in Ayatollah Mousavi Hospital in Zanjan, Iran during June-November 2017. A total of 95 women with preterm infants were selected by convenience sampling method. Data were collected using demographic and maternal role adaptation questionnaires. Finally, the obtained data were analyzed by the SPSS software employing descriptive statistics test and regression models at a confidence level of 95% (P<0.05). Results: Based on the results, the highest mean of maternal role adaptation belonged to the areas of child dependency and emotional development while the lowest mean was related to the area of concern and anxiety. In addition, the results demonstrated a significant correlation between the degree of maternal role adaptation and its areas such as family income, maternal and parents level of education, parents occupational status, birth weight, Apgar score, the gender of the infant, and delivery method. Conclusion: In general, the adaptation of mothers with preterm infants was low in the area of concern and anxiety compared to the other areas. Therefore, planning appropriate interventions to strengthen the maternal role is of great importance for the parents who have preterm infants, low level of education, and are unemployed with insufficient income.